Porphyromonas gingivalis: A key role in Parkinson's disease with cognitive impairment? - Li, Dongcheng; Ren, Tengzhu; Li, Hao; Liao, Geng; Zhang, Xiong (Frontiers in Neurology, 2022)
Cognitive impairment (CI) is a common complication of Parkinson's disease (PD). The major features of Parkinson's disease with cognitive impairment (PD-CI) include convergence of α-Synuclein (α-Syn) and Alzheimer's disease (AD)-like pathologies, neuroinflammation, and dysbiosis of gut microbiota. Porphyromonas gingivalis (P. gingivalis) is an important pathogen in periodontitis. Recent research has suggested a role of P. gingivalis and its virulence factor in the pathogenesis of PD and AD, in particular concerning neuroinflammation and deposition of α-Synuclein (α-Syn) and amyloid-β (Aβ). Furthermore, in animal models, oral P. gingivalis could cause neurodegeneration through regulating the gut-brain axis, suggesting an oral-gut-brain axis might exist. In this article, we discussed the pathological characteristics of PD-CI and the role of P. gingivalis in them.